Possible correlation between bile salt hydrolysis and ahl deamidation: staphylococcus epidermidis RM1, a potent quorum quencher and bile salt hydrolase producer - Mukherji, Ruchira; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2015)
The aim of the present work was to isolate a bile salt hydrolase (BSH) producer from fermented soy curd and explore the ability of the BSH produced to cleave bacterial quorum sensing signals. Bacterial isolates with possible ability to deconjugate bile salts were enriched and isolated on De Man, Rogosa and Sharpe (MRS) medium containing 0.2 % bile salts. BSH-producing positive isolate with orange-pink-pigmented colonies was isolated and was identified as a strain of Staphylococcus epidermidis using biochemical and phylogenetic tools. S. epidermidis RM1 was shown to possess both potent BSH and N-acyl homoserine lactone (AHL) cleavage activity. Genetic basis of this dual-enzyme activity was explored by means of specific primers designed using S. epidermidis ATCC 12228 genome as template. It was observed that a single enzyme was not responsible for both the activity. Two different genetic elements corresponding to each of the enzymatic activity were successfully amplified from the genomic DNA of the isolate.
Keywords: AHL acylase; Bile salt hydrolase; CV026; Quorum quenching; Staphylococcus epidermidis

Structural and enzymatic analysis of a dimeric cholylglycine hydrolase like acylase active on N-acyl homoserine lactones - Philem, Pushparani D.; Yadav, Yashpal; Sunder, Avinash Vellore; Ghosh, Deepanjan; Prabhune, Asmita; Ramasamy, Sureshkumar (Biochimie, 2020)
The prevalence of substrate cross-reactivity between AHL acylases and beta-lactam acylases provides a glimpse of probable links between quorum sensing and antibiotic resistance in bacteria. Both these enzyme classes belong to the N-terminal nucleophile (Ntn)-hydrolase superfamily. Penicillin V acylases alongside bile salt hydrolases constitute the cholylglycine hydrolase (CGH) group of the Ntn-hydrolase superfamily. Here we report the ability of two acylases, Slac1 and Slac2, from the marine bacterium Shewanella loihica PV4 to hydrolyze AHLs. Three-dimensional structure of Slac1 reveals the conservation of the Ntn hydrolase fold and CGH active site, making it a unique CGH exclusively active on AHLs. Slac1homologs phylogenetically cluster separate from reported CGHs and AHL acylases, thereby representing a functionally distinct sub-class of CGH that might have evolved as an adaptation to the marine environment. We hypothesize that Slac1 could provide the structural framework for understanding this subclass, and further our understanding of the evolutionary link between AHL acylases and beta-lactam acylases. (C) 2020 Elsevier B.V. and Societe Francaise de Biochimie et Biologie Moleculaire (SFBBM). All rights reserved.
Keywords: AHL acylase; Cholyolglycine hydrolase; Homodimer; Ntn-fold; Shewanella loihica-PV4